Nowa koncepcja patriotyzmu w ujęciu Jana Pawła II - Kindziuk, Milena (Studia Theologica Varsaviensia, 2018)
New concept of patriotism in the view of John Paul II Summary The concept of “patriotism” in general means the attitude of attachment and love for the homeland and the concern for its good and future. On this subject, Pope John Paul II devoted much space in his teaching, but he extended the meaning of the word “patriotism”. There is no doubt that he created a new, original concept of patriotism. This article is an analysis of the papal statements on this topic and is an attempt at answering the question of what John Paul II means to refer to patriotism in three aspects: homeland, the Decalogue and culture. It also allows us to better understand in what sense the Pope spoke about the theology of the homeland and why patriotism has a moral value for him.